Prussian Blue Analogue-Templated Nanocomposites for Alkali-Ion Batteries: Progress and Perspective - Zhou, Jian‑En; Li, Yilin; Lin, Xiaoming; Ye, Jiaye (Nano-Micro Letters, 2024)
Lithium-ion batteries (LIBs) have dominated the portable electronic and electrochemical energy markets since their commercialisation, whose high cost and lithium scarcity have prompted the development of other alkali-ion batteries (AIBs) including sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs). Owing to larger ion sizes of Na+ and K+ compared with Li+, nanocomposites with excellent crystallinity orientation and well-developed porosity show unprecedented potential for advanced lithium/sodium/potassium storage. With enticing open rigid framework structures, Prussian blue analogues (PBAs) remain promising self-sacrificial templates for the preparation of various nanocomposites, whose appeal originates from the well-retained porous structures and exceptional electrochemical activities after thermal decomposition. This review focuses on the recent progress of PBA-derived nanocomposites from their fabrication, lithium/sodium/potassium storage mechanism, and applications in AIBs (LIBs, SIBs, and PIBs). To distinguish various PBA derivatives, the working mechanism and applications of PBA-templated metal oxides, metal chalcogenides, metal phosphides, and other nanocomposites are systematically evaluated, facilitating the establishment of a structure–activity correlation for these materials. Based on the fruitful achievements of PBA-derived nanocomposites, perspectives for their future development are envisioned, aiming to narrow down the gap between laboratory study and industrial reality. Highlights: 1 The synthetic protocols of various Prussian blue analogue (PBA)-templated nanocomposites are discussed. 2 Alkali-ion storage mechanisms based on intercalation, alloying, or conversion reactions are analysed. 3 The properties of PBA-templated nanocomposites in alkali-ion batteries (AIBs) are evaluated and compared to outline the structure–activity correlation. 4 Perspectives for the future development of PBA-templated AIB electrodes are envisaged.